Influence of Ethical Leadership Practices in Developing Trust in Leaders: a Pilot Study on Malaysian Secondary Schools - Siva Vikaraman, Sharmini; Norhaini Mansor, Azlin; Izham Mohd Hamzah, Mohd (International Journal of Engineering and Technology, 2018)
Significant school leadership involves the ability to influence, motivate and; change teacher work behavior patterns towards achieving positive work place attitude and organizational goals. This quantitative correlational case study, aims at identifying the level of ethical leadership and trust in leader practiced by leaders, presenting facts and figures that determines the influence of ethical leadership practices in developing trust in leader that is presumed to lead to better work place behaviours. This cross-sectional study is a pilot survey which collected 31 national secondary school teachers’ perception on their school principal’s ethical leadership practices and their trust on their leaders through an on-line survey. The Ethical Leadership at Work and Trust in Leader questionnaire used in this study were strongly reliable with Cronbach Alpha values of 0.965 and 0.981 respectively.  Results showed level of ethical leadership practiced among secondary school principals and trust in their principal are both at high level. Findings also shows that ethical leadership correlated positively in the development of trust in leaders. The two practices of ethical leadership that showed very strong significant impact on developing trust in leaders were integrity and people orientation. The results encourage other researchers to explore the practice of ethical leadership with a larger sample, different variables and aims with the goal of improving leadership roles and teacher work performance.